First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations Prudential Insurance Company, who have promised us an annual subscription of £21, our application met with no response. Public Appeal An appeal was made through the medium of the Press in December, 1920, and resulted in a response which helped us to carry on our work up to 1921. The King contributed the sum of £100, which generous act made His Majesty the Royal Founder of the League. Endowment Fund of £100,000 An appeal for £100,000 Endowment Fund was launched at a Reception given by the Marchioness Curzon of Kedleston on Empire Day, 1921. The speakers included Viscount Burnham, the Bishop of Birmingham, Sir Bruce Bruce-Porter, Sir Johnston Forbes-Robertson, and the Hon. Organiser. The knowledge that the past year has been one of unparalleled stress and financial difficulties, alone compensates the Governing Council of the League for the small response made in answer to that appeal. Her Majesty's Patronage Her Majesty the Queen graciously gave her patronage to a Fête and Ball which were organised in November, 1921, in aid of the funds of the League. These were held at the historic Devonshire House, kindly lent by the present owners, Messrs. Holland, Hannen and Cubitt. Many of the Embassies and Legations also gave their patronage and were present at the Fête and Ball. The Fête was formally opened by The Right Hon. J.R. Clynes, M.P., Lay Councillor of the League, and was attended by Queen Amelie of Portugal. Mr. Louis N. Parker contributed a specially written prologue in verse, which was spoken by celebrated actresses. Messrs. Wolseley Motors, Ltd., very generously gave a 7 hp. Wolseley motor car to be competed for at the Fête in aid of the funds of the League. Messrs. Reville & Co., Ltd. with great generosity, constructed the prehistoric dresses from designs copied from the British Museum, and lent all the other modern costumes worn in the Pageant of Dress; and, through the munificent gift of £1,000 towards the expenses by Mrs. Simon Brand, the League benefited to the extent of £1,451 5s. 11d. A Sunday Concert at the Palladium Theatre, kindly lent by the National Sunday League, and organised by Miss Gladys Cooper and Miss Miriam Warner in aid of the funds of the League, resulted in a sum of £279 7s. 3d. Letters of Resignation. Letters of resignation have been received from the Hon. Secretary, Col. Innes, D.S.O., and the following members of the Medical Council and Recreation and Entertainment Committee : Marchioness Curzon of Kedleston, D.B.E., Appeal Directorship. Viscountess Barrington. Sir Victor Bonney. Col. Harrison, D.S.O. Lady Kent. Lady Savile of Rufford. Lady Kent was one of the founders of the League and a member of the Recreation and Entertainment Committee. The League has suffered a great loss in the death of the following members of its Medical and Lay Councils: Professor Sir German Sims Woodhead, K.B.E., LL.D., M.D. Professor Benjamin Moore, D.Sc., F.R.S. Sir John Kirk. Sir Arthur Pearson, Bart., C.B.E. Mr. William Baker. Lady Henry Somerset. Hon. Mrs. Lancelot Lowther. Miss Damer Dawson, D.B.E. 37 200/B/3/2/C693/1/71